Coordinated alterations in ribosomes and cytoplasmic membrane in sucrose-dependent, spectinomycin-resistant mutants of Escherichia coli. - Mizuno, T (1976)
Alterations in cytoplasmic membrane and ribosomes from sucrose-dependent spectinomycin-resistant (Sucd-Spcr) mutants of Escherichia coli, mutants that are resistant to spectinomycin in the presence of 20% sucrose but sensitive in the absence of sucrose, were studied. The protein composition of cytoplasmic membrane was analyzed by gel electrophoresis on polyacrylamide gel containing 8 M urea and 0.5% sodium dodecyl sulfate, which assured the reproducible separation of 28 protein bands. A major protein band, I-19, was missing in all cytoplasmic membrane preparations from 10 Sucd-Spcr mutants. Besides protein I-19, proteins I-13 and I-24 were missing in some mutants. On the other hand, the protein composition of cytoplasmic membrane from a sucrose-independent spectinomycin-resistant mutant was indistinguishable from that from the wild-type strain. The polypeptide synthetic activity of ribosomes from Sucd-Spcr mutants was resistant to spectinomycin. Studies on a revertant obtained from one of these mutants without any selection for sensitivity to spectinomycin revealed that a single mutation was responsible for both the ribosomal alteration, i.e., spectinomycin resistance, and the lack of protein I-19 in the cytoplasmic membrane. Studies on a transductant obtained with a Sucd-SPcr mutant as the donor also confirmed the single-mutation concept. It was concluded that in Sucd-SPcr mutants an alteration in the ribosomes caused the deletion of protein I-19 from cytoplasmic membrane.